Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/1746-1596-8-13
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic early event in chronic allograft nephropathy: increased but not decreased expression of MMP-9 gene

Abstract: ObjectiveThe infiltration of mononuclear cells and replication and migration of smooth muscle cells (SMCs) from media into the intima in the vascular wall are the cardinal pathological changes in the early stage of chronic allograft nephropathy (CAN). But the mechanism is unclear. Therefore we investigated the role of matrix metalloproteinase 9 (MMP-9) and its interaction with TGF-beta1, tubulointerstitial mononuclear cells infiltration and migration of SMCs in the early stage of CAN.MethodsKidneys of Fisher (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In addition, the significant correlation obtained between kidney proMMP9 and the GFR, a basic hallmark of renal dysfunction, suggests the involvement of MMPs in IF/TA development. In accordance with our results, an increased MMP9 expression in kidney allografts has been described as an early event in chronic allograft nephropathy in rats , in tight correlation with kidney mononuclear infiltration and TGFβ1 expression in the tubulo‐interstitium .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the significant correlation obtained between kidney proMMP9 and the GFR, a basic hallmark of renal dysfunction, suggests the involvement of MMPs in IF/TA development. In accordance with our results, an increased MMP9 expression in kidney allografts has been described as an early event in chronic allograft nephropathy in rats , in tight correlation with kidney mononuclear infiltration and TGFβ1 expression in the tubulo‐interstitium .…”
Section: Discussionsupporting
confidence: 92%
“…We speculate that the increase in active MMP-9 evident one week after KT likely originates from neutrophils in response to leukocyte activation inherent to I/R processes. This is supported by experimental studies demonstrating that MMP-9 promotes mononuclear cell infiltration in a rat model of early allograft nephropathy [43].…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the role of the serum MMP-9 level after day 20 in acute renal allograft rejection requires further exploration. In addition, it has been shown that MMP-9 expression in renal allografts is also upregulated during chronic allograft nephropathy [23,24], whereas the serum MMP-9 level at this stage remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, increased MMP-9 levels may promote the tissue infiltration of inflammatory cells, which then secrete more MMP-9 into the local environment, resulting in an amplification loop. In addition, it has been shown that increased MMP-9 expression may also induce the activation and replication of smooth muscle cells [23]. Therefore, MMP-9 might play an important role in the pathologic mechanism of renal allograft rejection, and thus could be a new potential target for treatment.…”
Section: Discussionmentioning
confidence: 99%